Interference by heterophilic antibodies in immunoassays: wrongincrease of myoglobin values - Bonetti, A.; Monica, C.; Bonaguri, C.; Gnocchi, et al., C. (Acta Biomedica Atenei Parmensis, 2008)
Aim of this work is to illustrate how analytical interference in immunoassay may produce serious errors in clinical laboratory results. The sophisticated quality assurance schemes used in many laboratories do not identify erroneous results arising from aberrant samples. Recently attention has been focused on the incidence and implication of false-positive results arising from the presence of certain substances in a patient’s serum that interfere with one or more steps in immunoassays. In this paper, we present the case of a 92 year-old woman whose plasma myoglobin concentrations falsely increased when measured using the Beckman Access assay. We demonstrated that heterophilic antibodies accounted for the falsely increased myoglobin values, and we suggest how to resolve such situations.